Role of luteinizing hormone in follicle deviation based on manipulating progesterone concentrations in mares - Gastal, E. L.; Bergfelt, D. R.; Nogueira, G. P. [UNESP]; Gastal, M. O.; Ginther, O. J. (My University, 1999)
The effects of several doses of progesterone on FSH and LH concentrations were used to study the role of the gonadotropins on deviation in growth rates of the two largest follicles during the establishment of follicle dominance. Progesterone was given to pony mares at a daily dose rate of 0 mg (controls), 30 mg (low dose), 100 mg (intermediate dose), and 300 mg (high dose). All follicles ≥ 6 mm were ablated at Day 10 (Day 0 = ovulation) to initiate a new follicular wave; prostaglandin F(2α) was given to induce luteolysis, and progesterone was given from Days 10 to 24. The low dose did not significantly alter any of the ovarian or gonadotropin end points. The high dose reduced (P < 0.05) the ablation-induced FSH concentrations on Day 11. Maximum diameter of the largest follicle (17.2 ± 0.6 mm) and the second- largest follicle (15.5 ± 0.9 mm) in the high-dose group was less (P < 0.04) than the diameter of the second-largest follicle in the controls (20.0 ± 1.0 mm) at the beginning of deviation (Day 16.7 ± 0.4). Thus, the growth of the two largest follicles was reduced by the high dose, presumably through depression of FSH, so that the follicles did not attain a diameter characteristic of deviation in the controls. The intermediate dose did not affect FSH concentrations. However, the LH concentrations increased in the control, low, and intermediate groups, but then decreased (P < 0.05) in the intermediate group to pretreatment levels. The LH decrease in the intermediate group occurred 2 days before deviation in the controls. The maximum diameter of the largest follicle was less (P < 0.0001) in the intermediate group (27.3 ± 1.8 mm) than in the controls (38.9 ± 1.5 mm), but the maximum diameter of the second-largest follicle was not different between the two groups (19.0 ± 1.1 vs. 20.3 ± 1.0 mm). Thus, the onset of deviation, as assessed by the second-largest follicle, was not delayed by the decrease in LH. Diameter of the largest follicle by Day 18 in the intermediate group (23.1 ± 1.6 mm) was less (P < 0.05) than in the controls (28.0 ± 1.0 mm). These results suggest that circulating LH was not involved in the initiation of dominance (inhibition of other follicles by the largest follicle) but was required for the continued growth of the largest follicle after or concurrently with its initial expression of dominance.
Keywords: follitropin; gonadotropin; luteinizing hormone; progesterone; prostaglandin f2 alpha; animal experiment; controlled study; growth rate; hormone determination; horse; luteolysis; nonhuman; ovary; ovary follicle development; priority journal; Animals; Female; Follicle Stimulating Hormone; Horses; Luteinizing Hormone; Ovarian Follicle; Ovulation; Progesterone; Time Factors; Animalia; Equus caballus; Fallopia